The Impact of Internal Marketing on Organizational Agility - ABOURDAN, FARAH (İstanbul Kültür Üniversitesi, 2025)
The purpose of this research is to examine the moderating effect of internal marketing on the relationship between internal marketing and the organizational agility in aviation sector in terms of responsiveness, competency, flexibility, and speed. Hence, a quantitative research design is adopted and an inductive method used to examine the interdependence of these factors. The target population is working in Istanbul Airport in Istanbul city, and intentional sampling of 140 participants is adopted to guarantee equal distribution of age, gender, qualification, and experiences. The data obtained from a structured questionnaire are analyzed by using SPSS software. The questionnaire developed through a systematic process of reviewing literature and multiple relevant studies is consisted of two scales; Internal Marketing Scale and Organizational Agility Scale. Demographic characteristics of the participants are described and multiple tests were run such as normality, reliability, and correlation and regression analysis, to determine the relationship among variables. The majority of the participants are male with 30-40 age range and had 1-3 years of working experience. Results showed that training, internal communication, teamwork, and motivation impact on organizational agility to a great extent. Training found to have a higher influence toward the agility factors such as Responsiveness, Competency, and Flexibility. Moreover, it also influenced organizational agility. The regression analysis supported that all internal marketing activities used in the study act as positive predictors of organizational agility. Internal marketing is considered an important determinant of organizational agility in technically complex industries such as aviation as pointed out in this research.
Keywords: Internal Marketing; Organizational Agility